Induction of Oxidative Stress by Subacute Oral Exposure of Cadmium Sulphate in Adult Poultry - Kant, Vinay; Mehta, Madhuri; Varshneya, Chandresh; Chauhan, Shivani (Brazilian Journal of Veterinary Pathology, 2011)
Cadmium has been recognized as one of the most toxic environmental and industrial pollutants. In the present study, twenty-four adult poultry birds were divided into four groups. In groups II, III and IV cadmium sulphate was given in drinking water at the dose rate of 100, 200 and 400 mg/L, respectively for 20 days to assess the effect of cadmium on the antioxidant defence system and lipid peroxidation (LPO) of erythrocytes of adult poultry birds as compared to group I, which was maintained at basal diet and normal drinking water. It was observed that the activities of erythrocyte superoxide dismutase (SOD) and catalase (CAT) increased during subacute cadmium toxicity. The activity of glutathione-S-transferase (GST) was non-significantly (P>0.05) increased in group II and III; but, non-significantly decreased in group IV. The level of blood glutathione (GSH) was significantly decreased in cadmium exposed birds. However, the lipid peroxidation (MDA) was significantly increased in the cadmium exposed groups as compared to group I. On the basis of present study, it could be concluded that cadmium exposure altered the activities of antioxidant enzymes of erythrocytes and produce oxidative stress by disturbing the oxidative and antioxidative balance of the adult poultry birds.